2020
DOI: 10.1007/s42438-020-00183-8
|View full text |Cite
|
Sign up to set email alerts
|

From ‘Illmatic’ to ‘Kung Flu’: Black and Asian Solidarity, Activism, and Pedagogies in the Covid-19 Era

Abstract: Trending social media has indicated that there are currently two pandemics: Covid-19 and racism. While this typology and terminology can be critiqued, it is rather clear that the virus and White supremacy are key concerns of social movements in various parts of the world, particularly in nation states that experienced European colonisation and imperialism. The wake of Covid-19 has perhaps brought greater attention and support to #BlackLivesMatter-oriented protest movements, including by those labelled people o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 43 publications
0
13
0
2
Order By: Relevance
“…The yellow peril narrative has intensified within recent years as China’s economic power on the world stage has grown and the U.S.’ stronghold has weakened (Li & Nicholson, 2021). As has been observed throughout the Trump administration and the COVID‐19 pandemic, Chinese people—as well as others who are racialized as “Chinese” or “Asian”—have been scapegoated for the growing inequities that have become more apparent amid a shift in global superpowers and a global health crisis (Chang, 2020). The rise in anti‐Asian sentiment throughout this time has significant implications for the sociopolitical and ethnic–racial identity development of Chinese American youth.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The yellow peril narrative has intensified within recent years as China’s economic power on the world stage has grown and the U.S.’ stronghold has weakened (Li & Nicholson, 2021). As has been observed throughout the Trump administration and the COVID‐19 pandemic, Chinese people—as well as others who are racialized as “Chinese” or “Asian”—have been scapegoated for the growing inequities that have become more apparent amid a shift in global superpowers and a global health crisis (Chang, 2020). The rise in anti‐Asian sentiment throughout this time has significant implications for the sociopolitical and ethnic–racial identity development of Chinese American youth.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Our findings suggest that the Asian-Black relationship became closer after COVID-19 and that it appeared to be divided into (1) black predators vs. Asian victims and (2) black and Asian victims. Previous studies have confirmed these two aspects (Chang, 2020;Ruiz et al, 2020;Solomos, 2021). We were unable to determine which aspects contributed to the relationship between Asian and Black people, but future studies with qualitative methods, such as in-depth interviews or focus group interviews, could be helpful in better understanding the impact of COVID-19 on the changes in their relationship.…”
Section: Discussionmentioning
confidence: 74%
“…According to Jandri c (2021, p. 262), '[w]hile postdigital really useful knowledge cannot be thought of without the pandemic, it reaches beyond the pandemic to the point where the pandemic experience is transformed from an object of research to an intrinsic part of our theories, approaches, research methodologies, and social struggles.' However, another snapshot is a cause for alarm: attacks on people of Asian descent are mounting around the world, encouraged, some think, by President Trump's continued reference to the 'Chinese virus' (Chang, 2020). Religious nationalism is on the rise (McLaren 2020), together with emerging reconfigurations of bio-neo-colonialism (Czerniewicz et al, 2020; see also Couldry & Mejias, 2019).…”
Section: Discussionmentioning
confidence: 99%